The roles of donation experience and advocacy: extending the organization–donor relationship model. Issue 1 (18th December 2020) - Harrison, Virginia; Buckley, Christen; Xiao, Anli
Abstract : Purpose: This study examines the stakeholder's experiences of two key groups: donors and donor-volunteers. The goals of this study are to (1) determine how donor experience affects organization–public relationships (OPRs) and its antecedents for these two groups and (2) extend the OPR model by considering new potential supportive behavioral intentions arising from OPR outcomes. Design/methodology/approach: Using data from a survey of self-identified donors and donor-volunteers, multiple regressions were performed to establish the possible effects of experience and advocacy on OPRs. Findings: Findings of this study support the idea that donation experience can be considered a potential antecedent for the OPR. The findings also support the idea that advocacy can be a valuable behavioral outcome resulting from OPR. Practical implications: Nonprofits are ever seeking to better connect with their donor and volunteer supporters. This study helps to show the value of donation experience and the importance of cultivating advocacy behaviors among these supporters. Originality/value: The study seeks to merge extant theory in communications and public policy to better understand the OPR model. Specifically, connecting OPR to the antecedent of donor experience and behavioral intentions like advocacy will help paint a stronger picture of donor–volunteer relationships with nonprofits.